From temporality to old practices: The (re)construction of the new senses for telejournalism in the convergent environment - Eduardo Rodrigues Bazi, Rogério (2015)
Technological advancement and the constant migration of TV programming to the internet have made it possible to realign customs, patterns, styles and ways of producing and watching television journalism. In this work, the objective is to initiate a process of reflection of the senses of some procedures that are still practiced by the telejornalismo said traditional in Brazil in the new conjuncture of the technological convergence. It is based on the concept of media convergence and brings reflections to the understanding of paradigmatic changes required for television journalism, in an attempt to (re)construct the meanings of journalistic production to a new consumer of information.